K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 5 2016

x very xấu

x=-6.79695431472081,

x=-1.92078708375378;

1 tháng 3 2022

gfvfvfvfvfvfvfv555

13 tháng 6 2021

Hơi căng 

30 tháng 11 2022

\(\dfrac{1}{1-x}+\dfrac{1}{1+x}+\dfrac{2}{1+x^2}+\dfrac{4}{1+x^4}+\dfrac{8}{1+x^8}+\dfrac{16}{1+x^{16}}\)

\(=\dfrac{1+x+1-x}{1-x^2}+\dfrac{2}{1+x^2}+\dfrac{4}{1+x^4}+\dfrac{8}{1+x^8}+\dfrac{16}{1+x^{16}}\)

\(=\dfrac{2+2x^2+2-2x^2}{1-x^4}+\dfrac{4}{1+x^4}+\dfrac{8}{1+x^8}+\dfrac{16}{1+x^{16}}\)

\(=\dfrac{4+4x^4+4-4x^4}{1-x^8}+\dfrac{8}{1+x^8}+\dfrac{16}{1+x^{16}}\)

\(=\dfrac{8+8x^8+8-8x^8}{1-x^{16}}+\dfrac{16}{1+x^{16}}\)

\(=\dfrac{16+16x^{16}+16-16x^{16}}{1-x^{32}}=\dfrac{32}{1-x^{32}}\)

13 tháng 11 2017

https://www.youtube.com/watch?v=cFZDEMTQQCs

j thế bạn

15 tháng 11 2019

1) 

=a^4+2a^2+1-a^2

=(a^2+1)^2-a^2

=(a^2-a+1)(a^2+a+1)

2)

=a^4+4b^4-4a^2b^2

=(a^2+2b^2)^2-4a^2b^2

=(a^2-2ab+2b^2)(a^2+2ab+2b^2)

3)

=(8x^2+1)^2-16x^2

=(8x^2-4x+1)(8x^2+4x+1).

4)

=x^5+x^4+x^3-x^3+1

=x^2(x^2+x+1)-(x-1)(x^2+x+1)

=(x^2-x+1)(x^2+x+1)

5).

=x^7-x+x^2+x+1

=x(x^6-1)+x^2+x+1

=x(x^3-1)(x^3+1)+x^2+x+1

=x(x-1)(x^2+x+1)(x^3+1)+x^2+x+1

=(x^2+x+1)[(x^2-x)(x^3+1)+1]

6)

=x^8-x^2+x^2+x+1

=x^2(x-1)(x^2+x+1)(x^3+1)+x^2+x+1

Xong nhóm x^2+x+1 vào.

7)

=x^4-(2x-1)^2

=(x^2-2x+1)(x^2+2x-1)

8)

=(a^8+b^8)^2-a^8b^8

=(a^8-a^4b^4+b^8)(a^8+a^4b^4+b^8).

3 tháng 12 2018

\(\dfrac{1}{x-1}-\dfrac{1}{x+1}-\dfrac{2}{x^2+1}-\dfrac{4}{x^4+1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)

\(=\dfrac{x+1-x+1}{x^2-1}-\dfrac{2}{x^2+1}-\dfrac{4}{x^4+1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)

\(=\dfrac{2}{x^2-1}-\dfrac{2}{x^2+1}-\dfrac{4}{x^4+1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)

\(=\dfrac{2\left(x^2+1-x^2+1\right)}{x^4-1}-\dfrac{4}{x^4+1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)

\(=\dfrac{4}{x^4-1}-\dfrac{4}{x^4+1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)

\(=\dfrac{4\left(x^4+1-x^4+1\right)}{x^8-1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)

\(=\dfrac{8}{x^8-1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)

\(=\dfrac{8\left(x^8+1-x^8+1\right)}{x^{16}-1}-\dfrac{16}{x^{16}+1}\)

\(=\dfrac{16}{x^{16}-1}-\dfrac{16}{x^{16}+1}\)

\(=\dfrac{16\left(x^{16}+1-x^{16}+1\right)}{x^{32}-1}\)

\(=\dfrac{32}{x^{32}-1}\)